The happiness project, tenth anniversary edition ebook Or, why i spent a year trying to sing in the morning, clean my closets, fight right, read aristotle, and generally have more fun. - Rubin, Gretchen (2018)
#1 New York Times Bestseller "An enlightening, laugh-aloud read. . . . Filled with open, honest glimpses into [Rubin's] real life, woven together with constant doses of humor."—Christian Science Monitor Gretchen Rubin's year-long experiment to discover how to create true happiness. Drawing on cutting-edge science, classical philosophy, and real-world examples, Rubin delivers an engaging, eminently relatable chronicle of transformation. This special 10 th Anniversary edition features a Conversation with Gretchen Rubin, Happiness Project Stories, a guide to creating your own happiness project, a list of dozens of free resources, and more. Gretchen Rubin had an epiphany one rainy afternoon in the unlikeliest of places: a city bus. "The days are long, but the years are short," she realized. "Time is passing, and I'm not focusing enough on the things that really matter." In that moment, she decided to dedicate a year to her happiness project. In this lively and compelling account—now updated with new material by the author—Rubin chronicles her adventures during the twelve months she spent test-driving the wisdom of the ages, current scientific research, and lessons from popular culture about how to be happier. Among other things, she found that novelty and challenge are powerful sources of happiness; that money can help buy happiness, when spent wisely; that outer order contributes to inner calm; and that the very smallest of changes can make the biggest difference. This updated edition includes: An extensive new interview with the author Stories of other people's life-changing happiness projects A resource guide to the dozens of free resources created for readers The Happiness Project Manifesto An excerpt from Rubin's bestselling book The Four Tendencies: The Indispensable Personality Profiles that Reveal How to Make Your Life Better (and Other People's Lives Better, Too)